The Yamabe problem on subdomains of even-dimensional spheres - Pacard, Frank (Topological Methods in Nonlinear Analysis, 1995)
We prove the existence of complete conformally flat metrics of constant positive scalar curvature on the complement in S^n of a finite number of (n-2)/2-dimensional smooth submanifolds, provided n ≥ 4 is even.